Systematic morphometric characterization of volcanic edifices using digital elevation models - Grosse, Pablo (2012)
Quantitative characterization of the size and shape of volcanic edifices is an essential step towards the understanding of factors controlling volcano growth and morphology. The recent advent of digital elevation models (DEMs) with worldwide coverage offers the opportunity to systematically document the morphometry of all types of volcanoes using quantitative well-formalized methodologies. We present a methodology for the morphometric characterization of volcanic edifices. After reviewing previous studies on volcano morphometry and the various existing DEM sources, we describe an integrated procedure that uses a DEM and its derived products (slope, curvature) to extract a coherent set of morphometric parameters for a given volcanic edifice. Edifice boundaries are manually defined by searching for breaks in slope around the base. The parameters describe the overall size (basal and summit region area and widths, height, volume), planar shape (ellipticity and irregularity index of elevation contours), profile shape (height?width ratios) and slope of the edifice. Similar parameters for relatively large (depending on DEM spatial resolution) summit craters/calderas are also computed. Slope values and ellipticity and irregularity indexes are extracted for successive height intervals providing detailed information of volcano shape as a function of height. The number of secondary peaks is also estimated. The method is tested on thirteen composite volcanoes in Nicaragua using three DEM datasets (90 m SRTM, 30 m ASTER G-DEM and an 80 m topographic map-derived DEM) and the resulting parameters are evaluated in terms of boundary delineation and DEM source. Finally, the parameters obtained for the Nicaraguan volcanoes are discussed as an illustrative example of the type of data and information that can be extracted systematically for volcanoes worldwide.